Nanowires applications, chemistry, materials and technologies - Gupta, Ram K. (CRC Press, Taylor and Francis Group, 2023)
"This comprehensive resource covers the fundamentals of synthesis, characterizations, recent progress, and applications of nanowires for many emerging applications. Early chapters address their unique properties and morphology that enable their electronic, optical, and mechanical properties to be tuned. Later chapters address future perspectives and future challenges in areas where nanowires could provide possible solutions. All chapters are written by global experts, making this a suitable textbook for students and an up-to-date handbook for researchers and industry professionals working in physics, chemistry, materials, energy, biomedical, and nanotechnology"--